Endothelial Dysfunction in Childhood Cancer Survivors: A Narrative Review - Marco Crocco; Giuseppe d’Annunzio; Alberto La Valle; Gianluca Piccolo; Decimo Silvio Chiarenza; Carolina Bigatti; Marta Molteni; Claudia Milanaccio; Maria Luisa Garrè; Natascia Di Iorgi; Mohamad Maghnie (Life, 2021)
Assessment of endothelial dysfunction in cancer survivors may have a role in the early identification of non-communicable diseases and cardiovascular late effects. Oncological therapies may impair endothelial function. Therefore, in patients such as childhood cancer survivors who could benefit from early cardioprotective pharmacological interventions, it is essential to monitor endothelial function, even if the optimal methodology for investigating the multifaceted aspects of endothelial dysfunction is still under debate. Biochemical markers, as well as invasive and non-invasive tools with and without pharmacological stimuli have been studied. Human clinical studies that have examined lifestyle or cancer treatment protocols have yielded evidence showing the involvement of lipid and lipoprotein levels, glycemic control, blood pressure, adiposity, inflammation, and oxidative stress markers on the state of endothelial health and its role as an early indicator of cardiometabolic risk. However, with regards to pharmacological interventions, cautious interpretation of the result attained whilst monitoring the endothelial function is warranted due to methodological limitations and substantial heterogeneity of the results reported in the published studies. In this narrative review, an overview of evidence from human clinical trials examining the effects of cancer therapies on endothelial disease is provided together with a discussion of endothelial function assessment using the different non-invasive techniques available for researchers and clinicians, in recent years.